An Alternative Particle Filter-Driven ADR for Mobile Devices in LoRaWAN Networks - Neto, Geraldo A. Sarmento; da Silva, Thiago A. Ribeiro; Veloso, Artur F. da S.; de Abreu, Pedro Felipe; Mendes, Luis H. de O.; Rabelo, Ricardo A. L.; dos Reis Jr, J. Valdemir (Journal of Internet Services and Applications, 2025)
LoRaWAN is a leading LPWAN technology for Internet of Things applications, known for its long-range communication and low-power consumption. Its ADR mechanism optimizes performance by adjusting transmission parameters, such as spreading factor and transmission power, based on network conditions. However, ADR faces significant limitations in environments with mobile end devices, where fluctuating signal quality leads to increased packet loss, inefficient energy usage, and reduced communication reliability. To address these challenges, PF-ADR, an alternative ADR scheme, is proposed for LoRaWAN networks with mobile devices. PF-ADR employs a particle filter to estimate a representative SNR value, maintaining multiple hypotheses of the communication channel state to enable more precise parameter adjustments. Simulations conducted under various scalability conditions reveal that PF-ADR achieves up to 29.5% higher packet delivery ratio compared to M-ADR, and 52.17% more than the standard ADR, while demonstrating a 43.19% improvement in energy efficiency over MB-ADR. Additionally, the algorithm reduces packet loss due to signal degradation while maintaining scalable performance in large networks. These results highlight the potential of PF-ADR to enhance communication reliability and energy efficiency in dynamic mobile environments.